webQDA: qualitative data analysis software: usability assessment - Costa, António Pedro (2018)
The use of qualitative analysis to support software has been growing. The integration of these types of tools in research is accompanied by an increase in the number of software packages available. Depending on the design and research questions, researchers can explore various solutions available in the market. Thus, it is urgent to ensure that these tools, apart from containing the necessary functionality for the purposes of research projects, are also usable. This study presents an assessment of the usability of the qualitative data analysis software webQDA® (version 2.0). To assess its usability, the System Usability Scale (SUS) was used. The results indicate that the current version is "acceptable" in terms of usability. We therefore hope, with this assessment, to make decisions so as to improve the usability of the new version of webQDA® (version 3.0).